Changes in the digital scholarly environment and issues of trust: An exploratory, qualitative analysis. Issue 3 (May 2016) - Watkinson, Anthony; Nicholas, David; Thornley, Clare; Herman, Eti; Jamali, Hamid R.; Volentine, Rachel; Allard, Suzie; Levine, Kenneth; Tenopir, Carol
Highlights: Digital transition had resulted in changes in researcher behaviour. It is now easier for scientists to discover and disseminate research. The way scientists exercise trust has not changed. Metrics are less important than experience and personal recommendation. Abstract: The paper reports on some of the results of a research project into how changes in digital behaviour and services impacts on concepts of trust and authority held by researchers in the sciences and social sciences in the UK and the USA. Interviews were used in conjunction with a group of focus groups to establish the form and topic of questions put to a larger international sample in an online questionnaire. The results of these 87 interviews were analysed to determine whether or not attitudes have indeed changed in terms of sources of information used, citation behaviour in choosing references, and in dissemination practices. It was found that there was marked continuity in attitudes though an increased emphasis on personal judgement over established and new metrics. Journals (or books in some disciplines) were more highly respected than other sources and still the vehicle for formal scholarly communication. The interviews confirmed that though an open access model did not in most cases lead to mistrust of a journal, a substantial number of researchers were worried about the approaches from what are called predatory OA journals. Established researchers did not on the whole use social media in their professional lives but a question about outreach revealed that it was recognised as effective in reaching a wider audience. There was a remarkable similarity in practice across research attitudes in all the disciplines covered and in both the countries where interviews were held.